The inhibition of hepatic bile acids transporters Ntcp and Bsep is involved in the pathogenesis of isoniazid/rifampicin-induced hepatotoxicity. (13th June 2015) - Guo, Yao Xue; Xu, Xue Fei; Zhang, Qi Zhi; Li, Chun; Deng, Ye; Jiang, Pei; He, Lei Yan; Peng, Wen Xing
Abstract: Co-treatment of isoniazid (INH) and rifampicin (RFP) is well known for clinically apparent liver injury. However, the mechanism of INH/RFP-induced liver injury is controversial. Emerging evidence shows links between inhibition of bile acids transporters and drug-induced liver injury (DILI). The present study investigates whether sodium taurocholate cotransporting polypeptide (NTCP/Ntcp; SLC10A1) and bile salt export pump (BSEP/Bsep; ABCB11) are involved in the anti-tuberculosis medicines induced liver injury. ICR female mice were intragastrically treated with INH (50 or 100 mg/kg), RFP (100 or 200 mg/kg), or the combination of INH/RFP (50 + 100 mg/kg or 100 + 200 mg/kg) for 14 consecutive days. Liver histopathological examination, serum biochemical and liver malondialdehyde tests were evaluated. Apparent histopathological alterations and hepatic oxidative stress showed in INH (100 mg/kg), RFP (200 mg/kg) and their combination group. The hepatoxic effect was also indicated by increased serum biomarkers, such as aspartate transaminase (AST), alanine aminotransferase (ALT), alkaline phosphatase (ALP), direct bilirubin (DBil), total bilirubin (TBil) and total bile acids (TBA). Both doses of INH/RFP administration significantly down-regulated the expression of Ntcp and Bsep in liver. Furthermore, the combination of INH and RFP displayed stronger effect on the expression of Ntcp compared with the corresponding dose of INH or RFP alone. In conclusion, down-regulated expression of hepatic Ntcp and Bsep might play an important role in the development of INH and RFP induced liver injury.